1988
DOI: 10.1073/pnas.85.19.7317
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of the human M2 mitochondrial autoantigen of primary biliary cirrhosis: dihydrolipoamide acetyltransferase.

Abstract: Primary biliary cirrhosis is a chronic, destructive autoimmune liver disease of humans. Patient sera are characterized by a high frequency (greater than 95%) of autoantibodies to a Mr 70,000 mitochondrial antigen, a component of the M2 antigen complex. We have identified a human cDNA clone encoding the complete amino acid sequence of this autoantigen. The predicted structure has significant similarity with the dihydrolipoamide acetyltransferase (EC 2.3.1.12) of the Escherichia coli pyruvate dehydrogenase multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
0
2

Year Published

1989
1989
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(130 citation statements)
references
References 22 publications
2
126
0
2
Order By: Relevance
“…3 In addition, recombinant proteins consisting of the 4 domains of human PDC-E2 were also used in this study. 17 Briefly, the EcoRI fragment (nucleotides 745-2,536) of the human PDC-E2 complementary DNA clone 3 was digested into 4 fragments with restriction endonucleases and subcloned into frame-matched derivatives of pBTA224 (fragment A, C, and D) and pGEX (fragment B).…”
Section: Epitope Mapping Using Recombinant Truncated Fragments Of Pdcmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In addition, recombinant proteins consisting of the 4 domains of human PDC-E2 were also used in this study. 17 Briefly, the EcoRI fragment (nucleotides 745-2,536) of the human PDC-E2 complementary DNA clone 3 was digested into 4 fragments with restriction endonucleases and subcloned into frame-matched derivatives of pBTA224 (fragment A, C, and D) and pGEX (fragment B).…”
Section: Epitope Mapping Using Recombinant Truncated Fragments Of Pdcmentioning
confidence: 99%
“…Earlier studies from both our laboratory and others have shown that serum AMA react with a series of highly conserved mitochondrial proteins, in particular the 2-oxo acid dehydrogenase complexes, including the dihydrolipoamide acetyltransferase component of the pyruvate dehydrogenase complex E2 (PDC-E2), the branched chain 2-oxo acid dehydrogenase complex E2 (BCOADC-E2), and the 2-oxoglutarate dehydrogenase complex E2 (OGDC-E2). [2][3][4] The major serum autoantibody reactivity is directed against the 74-kd PDC-E2 protein; more than 90% of PBC patients have serum AMA directed against PDC-E2.…”
mentioning
confidence: 99%
“…Whilst there are some precedents for autoantigens existing as components of multimeric complexes, for example the pyruvate dehydrogenase complex, of M r 8 2 10 6 , for which the E 2 subunit is the major reactant with primary biliary cirrhosis sera [27], a requirement for a multimeric form of a molecule for autoantigenic reactivity is exceptional. One precedent is the proliferating cell nuclear antigen (PCNA) which appears to require a trimeric structure for autoantigenic reactivity, since recombinant proteins that contain mutations or deletions preventing formation of trimers are non-reactive with autoantibodies [28].…”
Section: Discussionmentioning
confidence: 99%
“…Among these autoantigens, human PDC-E2 has been cloned, sequenced and expressed [8,9]. Previous studies of epitope mapping have relied on whole sera and have suggested that the immunodominant epitope lies within the inner lipoyl domain of the molecule and may include a large conformational component [9,10].…”
Section: Introductionmentioning
confidence: 99%